P3.080 Prevalence of C. Trachomatis, N. Gonorrheae, T. Vaginalis, C. Albicans, Syphilis, Bacterial Vaginosis & HIV in a Population of Women with Symptoms of Lower Genital Infections in Bogotá, Colombia 2010. (13th July 2013) - Muller, E Angel; Rodriguez, A; Nuñez-Forero, L; Moyano, L; González, P; Osorio, E; Diaz, L; Rodriguez, N; Parra, A Ruiz; Duarte, H Gaitan
Abstract : Objetives: To determine the prevalence and aetiology of lower genital tract infections (LGTIs) in symptomatic women of reproductive age and describe the risk factors. Methods: Cross sectional study. Symptomatic women who consulted at three ambulatory care centres in Bogotá, Colombia. Exclusions: pregnancy, hysterectomy, antibiotics in the previous 7 days. Samples were obtained for etiologic diagnosis using gold standard tests for: bacterial vaginosis (VB) by Nugent's criteria; blood agar culture for Candida and a wet smear and In pouch™ culture for T. vaginalis. PCR for C. trachomatis (CT) and N. gonorroheae (NG), and serologic tests for syphilis (RPR, TPHA) and HIV. Results: 1385 women were recruited from February to December 2010. 115 (8.3%) of them were sexual workers. A LGTI was confirmed in 731 (52.7%); 560 (40.4%) had an endogenous infection and 170 (12.3%) a sexually transmitted infection (STI). The most frequent aetiology was VB in 549 (39.6%), followed by candidiasis in 153 (11%). CT was detected in 134 (9.7%), NG in 19 (1.4%), Trichomonas by wet smear in 11 (0.8%) and by culture in 8/634 (1.2%), syphilis in 12 (0.8%) and HIV in 1 case. The risk factors of STI are: sex workers (OR: 2.0, CI 95% 1.2 – 3.3), younger age (28 ± 7.8 vs. 32 ± 8.9 (mean ± SD), no health insurance (23.5 vs. 15.4%) and alcohol users (OR: 2.6 (95% CI: 1.4 – 4.5)) Conclusions: 52.7% of women who consult for symptoms of LGTIs an aetiology can be identified, being BV the most common and Chlamydia the most frequent STI. Almost the same number of women (47.3%) has no specific aetiology identified, even with the use of gold standard diagnostic technology. This information should be used by policy makers and clinicians for prioritisation of prevention and diagnosis of LGTIs and use of syndromic management